Neutrophil-Lymphocyte Ratio as a Predictor of Severity of Acute Pancreatitis - Gadar U. Arevik, Harutyun L. Marine (Academic Journal of Clinicians, 2025)
Severe acute pancreatitis is a significant contributor to morbidity and mortality, with a 48% rate in severe instances. The prediction of severe pancreatitis presentations has resulted in the implementation of various severity scoring systems. This study seeks to ascertain the correlation between the neutrophil-lymphocyte ratio and the severity of acute pancreatitis. A retrospective descriptive cross-sectional study conducted during the period from January 2015 to October 2021. Demographic information, etiology, diagnostic criteria, neutrophil-lymphocyte index, acute and systemic sequelae, and outcomes were collected. Univariate analysis, ROC curve, and Youden index were conducted to determine a cut-off point as an indicator of severity. Ninety patients were studied. Predominant etiology: Biliary pancreatitis. 46.6% of patients exhibited moderate to severe symptoms. Hyperglycemia and type 2 diabetes mellitus were correlated with severity. Peripancreatic collections and abdominal septic shock were the most prevalent consequences. A neutrophil-lymphocyte index over 4.066 correlated with severe pancreatitis, with a sensitivity of 89% and a specificity of 78%. In Conclusion, a threshold for the neutrophil-lymphocyte index indicative of severity in acute pancreatitis was established.